2016
DOI: 10.1261/rna.057943.116
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of the TYW3/Taw3 class of SAM-dependent methyltransferases

Abstract: S-adenosylmethionine (SAM)-dependent methyltransferases regulate a wide range of biological processes through the modification of proteins, nucleic acids, polysaccharides, as well as various metabolites. TYW3/Taw3 is a SAM-dependent methyltransferase responsible for the formation of a tRNA modification known as wybutosine and its derivatives that are required for accurate decoding in protein synthesis. Here, we report the crystal structure of Taw3, a homolog of TYW3 from Sulfolobus solfataricus, which revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Several genes identified in our analyses encoded RNA binding and processing proteins, including a PPR protein, a nucleotidyltransferase, a NTP_transf_2 domain protein, a NYN domain protein, a class I SAM-dependent methyltransferase and a YbaK/prolyl-tRNA synthetase (Anantharaman and Aravind, 2006 ; Bartholow et al, 2014 ; Yamashita et al, 2014 ; Manna, 2015 ; Currie et al, 2017 ). Notably PPR proteins are involved in RNA splicing, editing, processing and translation.…”
Section: Resultsmentioning
confidence: 98%
“…Several genes identified in our analyses encoded RNA binding and processing proteins, including a PPR protein, a nucleotidyltransferase, a NTP_transf_2 domain protein, a NYN domain protein, a class I SAM-dependent methyltransferase and a YbaK/prolyl-tRNA synthetase (Anantharaman and Aravind, 2006 ; Bartholow et al, 2014 ; Yamashita et al, 2014 ; Manna, 2015 ; Currie et al, 2017 ). Notably PPR proteins are involved in RNA splicing, editing, processing and translation.…”
Section: Resultsmentioning
confidence: 98%
“…We propose to name these enzymes Taw3c. In recent work, the crystal structure of putativeTaw3c protein from S. solfataricus was solved and revealed a novel α/β fold, which constitutes a new class of methyltransferases composed of SHS2, RAGNYA fold domains, and an N-terminal extension (PDB 1TLJ, [50], Figure 3). Interestingly, total tRNA isolated from S. cerevisiae tyw3 mutant and possessing yW-86 was not a substrate for SsTaw3c enzyme, clearly distinguishing it from yeast Tyw3 or Pyrococcus Taw3a proteins.…”
Section: Formation Of Img-14 By Taw1 Enzymementioning
confidence: 99%
“…In the aforementioned work [50], the structure of SsTaw3c was compared with the other three Taw3 structures deposited into PDB: Archaeoglobus fulgidus (PDB 2QG3), Pyrococcus horikoshii (PDB 2IT2), and Aeropyrum pernix (PDB 2DVK)). It was shown that all three structures share the same domain architecture and overall fold as SsTaw3.…”
Section: Formation Of Img-14 By Taw1 Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, also the class I SAM-dependent methyltransferase, which regulates a wide range of biological processes through the modification of biological macromolecules such as DNA, RNA, polysaccharides, and lipids (Currie et al, 2017), enriched those clusters.…”
Section: Discussionmentioning
confidence: 99%